Main Lines of Chinese Foreign Policy from the Opening to the Present - Martín, Rafael (Sinología hispánica. China Studies Review, 2019)
The history of the international relations of the People’s Republic of China contains lines of action that should not go unnoticed. These lines are the consequence of the extraordinary circumstances that have surrounded the country since its proclamation in 1949, then within the framework of the Cold War, but with a huge burden of personality and ideology. Chinese history and culture, thus, have shaped their own context from which the events that took place around them were understood. The energetic personality of Mao and his ideology, the pragmatism of Deng Xiaoping, and the vicissitudes experienced by the world from the Cold War to the present, have created a cosmos of diverse circumstances that nevertheless do not detract from the fact that Chinese diplomacy has wellmarked lines of action, flexible, but immutable in time, and which are typical of their personality and idiosyncrasy. To understand the international relations of a country is to understand the soul of its citizens, because this is often reflected in the others. China has lived these years its inclusion in the new global world without forgetting the patterns that were already recognizable in distant times.